Herbal medicines in dentistry - Polo, Ana Bárbara; Tomé, Beatriz Vilela; Silva, Cássia Pereira da; Tavares, Luciana Cláudia Diniz; Paula, Marcelle Silva Alves de; Oliveira, Mariana Simões de; Moraes, Matheus Fernandes Lasneau; Júnior, Michel de Oliveira Salles; Cardoso, Millena Machado; Gomes, Taleessa Vieira; Clemente, Vitória Batista; Apolônio, Ana Carolina Morais (Seven Editora, 2024)
The popular use of medicinal plants has brought important knowledge of their biological applications. Thus, therapeutics using medicinal plants was legally called Phytotherapy. In dentistry, herbal medicines still have a timid participation, although much research is being developed in the area. The main applications in dentistry are in the relief of pain and inflammation, the treatment of periodontal disease, and the treatment of caries. In this chapter we will discuss a little about the aspects involved in the use of phytotherapy in dentistry. DOI:https://doi.org/10.56238/sevened2024.007-057